EFFECTIVENESS OF AUDIO-VISUAL AIDS FOR TEACHING ENGLISH POETRY AT SECONDARY LEVEL (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The importance of language is gradually being recognized by those who are keenly interested in the process of real education. In India one of the main functions of education is to develop in the individual an ability to communicate with others as well as to express himself in a suitable language. Language is a mean of communication and the most valuable possession of human race. In language human experiences are recorded and transmitted to the new generation.